2004
DOI: 10.1111/j.1365-2958.2003.03972.x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc is a key factor in controlling alternation of two types of L31 protein in the Bacillus subtilis ribosome

Abstract: SummaryWe have analysed changes in the composition of ribosomal proteins during cell growth in Bacillus subtilis . Ribosome fractions were prepared from B. subtilis cells at different phases of growth and were separated by radical-free and highly reducing (RFHR) twodimensional polyacrylamide gel electrophoresis. We identified 50 ribosomal proteins, including two paralogues of L31 protein (RpmE and YtiA). Although the ribosome fraction extracted from exponentially growing cells contained RpmE protein, this prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
141
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 123 publications
(148 citation statements)
references
References 32 publications
7
141
0
Order By: Relevance
“…1). From these findings, together with the observation that YtiA binds to the 50S subunit of the ribosome, 62) we concluded that B. subtilis expresses two types of ribosomal L31 protein differentially and switches between them during different phases of growth.…”
Section: Identification Of Switching Between Two Types Of L31 Proteinmentioning
confidence: 90%
See 3 more Smart Citations
“…1). From these findings, together with the observation that YtiA binds to the 50S subunit of the ribosome, 62) we concluded that B. subtilis expresses two types of ribosomal L31 protein differentially and switches between them during different phases of growth.…”
Section: Identification Of Switching Between Two Types Of L31 Proteinmentioning
confidence: 90%
“…By matrix assisted laser desorption ionization time-of-flight mass spectrometry (MALDI TOF-MS) and N-terminal sequence analyses, 51 spots were assigned to ribosomal proteins with duplicated spots for L29 (L29 and L29m, the latter detected only in the ribosomal fractions of exponentially growing cells). 62) Moreover, YvyD and YugI, which are known as general stress proteins, 63,64) were identified in the ribosomal fractions. 62) YvyD was found in the ribosomal fractions prepared from cells in stationary phase.…”
Section: Proteomic Analysis Of Ribosomal Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…In many bacteria, zinc depletion causes inactivation of zinc-specific Zur to derepress zinc transporter genes (6). In Gram-positive bacteria, genes for zincless ribosomal proteins are derepressed to replace zinc-bound paralogs as a way of mobilizing zinc (7)(8)(9)(10)(11)(12). Coelibactin, a putative zincophore, has been recently reported to be regulated by Zur in Streptomyces coelicolor (13,14).…”
mentioning
confidence: 99%